Decision-Making of the ECB: Reform and Voting Power - Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
The ECB reform is designed to meet the challenges of an enlarged monetary union in the ECB Council. The reform is assessed by analysing alternatives for the classification of governors into groups of the rotation scheme like the synchronisation of the economic development of the member states. In a second approach, voting power indices are assigned to the governors allocated to the different groups instead of voting weights. Special attention is given to the difference between the political weight of a governor and the economic and population weight of its country of origin.
Keywords: E58; 330; ECB; reform; rotation scheme; voting power indices; Zentralbank; Reform; Abstimmung; Macht; Landesgrösse; Europäische Wirtschafts- und Währungsunion; EU-Staaten; Power index